Gas chromatography: a useful tool for bakery products differentiation. - Albuquerque, T.G. (2018)
Bakery products (cookies, biscuits, cakes, crackers, bread and savoury snacks) are highly appreciated and frequently consumed by all age consumers, usually as part of breakfast, mid-morning and afternoon snacks. The main ingredients of bakery products are: wheat flour, sugar, fat, water and salt. With respect to fat, besides the total amount, it is very important to evaluate its quality, namely the fatty acid profile. One of the most suitable techniques to evaluate the fatty acids composition of a food is gas chromatography coupled to flame ionization detection. The aim of this study was to evaluate if gas chromatography is a useful tool for bakery products differentiation, with respect to their fatty acids profile and impact on human nutrition. Therefore, 30 bakery products from six categories (“Maria” cookies, plain salty cookies, coated chocolate cookies, brioche filled with chocolate, brioche without filling and with chocolate chips, and French croissants) and from different brands, were acquired in supermarkets from Lisbon region. Total fat content was determined by acid hydrolysis and Soxhlet extraction with petroleum ether. Fatty acids methyl esters were obtained by cold transesterification and analysed by gas chromatography with flame ionization detection. Most of the analysed foods (83%) have a higher content of saturated than monounsaturated and polyunsaturated fatty acids. For all the studied categories considerable differences were observed in the fatty acid profile, except for brioche with chocolate chips. In “Maria” cookies, plain salty cookies and coated chocolate cookies, at least one sample had as major fatty acids the monounsaturated instead of saturated. In the brioche filled with chocolate category, for two of the analysed samples the major fatty acids were saturated, while for the other sample predominated the polyunsaturated fatty acids. In conclusion, gas chromatography is a useful technique to differentiate the nutritional quality of bakery products, as well as to estimate the potential impact of these foods on public health. Furthermore, it was possible to conclude that food industry should address new strategies to reformulate their products. According to the obtained results, it is possible to produce similar foods with healthier nutritional features.